A comparative investigator-initiated pilot study on the efficacy and safety of biodegradable microneedle acupuncture and conventional intradermal acupuncture for dry eye patient: A superiority, assessor-blinded, randomized controlled trial. Issue 47 (25th November 2022) - Song, Ji-Hoon; Park, Soo-Yeon
Abstract : Background: The prevalence of dry eye, which is a common lacrimal disease, is steadily increasing in modern society. However, fundamental treatment for it has not yet been established. This study aims to assess the efficacy and safety of a novel medical device, the biodegradable microneedle acupuncture (BMA), using a traditional intradermal acupuncture needle as the control acupuncture for dry eye. Method: This study will be an investigator-initiated, assessor-blinded, comparative, superiority pilot randomized controlled trial. A total of 30 patients with dry eye will be randomly assigned to the experimental or the control group in equal proportion. For the experimental group, the BMA will be applied to both sides of 5 acupoints including BL2, GB14, TE23, EX-HN5, and ST1. For the control group, conventional intradermal acupuncture will be applied to the same acupoints. The needles will be attached for 4 hours. Over 4 weeks, both the interventions will be performed 12 times in total. The primary outcome would be the ocular surface disease index. The secondary outcomes would be the visual analog scale for subjective symptoms, quality of life, Schirmer I test, and general assessment. Discussion: The findings of this study on the efficacy and safety of the BMA would be helpful for patients with dry eye in clinical practice. Further, these results would provide for the foundation of a large-scale BMA study.